Isolation of β-Lactam & Colistin Resistant Bacteria and associated β-Lactamase & CLR Gene from animal originated food - Paul, Moumita; Tahiat, Tasfia; Khan, Nabila; Tasnim, Samiha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.